One pot solvent free synthesis and in vitro antitubercular screening of 3-aracylphthalides against mycobacterium tuberculosis - Limaye, Rohan A.; Kumbhar, Virendra B.; Natu, Arun D.; Paradkar, Madhusudan V.; Honmore, Varsha S.; Chauhan, Rubia R.; Gample, Suvarna P.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2013)
One pot synthesis of 3-Aracylphthalide was accomplished in good yield by reacting 2-carboxy benzaldehyde with various aromatic methyl ketones in presence of methane sulphonic acid. Various phthalides thus obtained were characterized with spectral techniques. These phthalides were subjected to in vitro antitubercular screening against Mycobacterium tuberculosis H37Ra (MTB) by using XRMA protocol. Among the phthalides screened, four exhibited half maximal inhibitory concentration (IC50) in the range of 0.81-1.24 mu g/ml thereby providing potential lead compounds for future drug discovery studies. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 3-Aracylphthalide; Antitubercular activity; Methane sulphonic acid; One pot synthesis

Antifungal dimeric chalcone derivative kamalachalcone E from Mallotus philippinensis - Kulkarni, Roshan R.; Tupe, Santosh G.; Gample, Suvarna P.; Chandgude, Macchindra G.; Sarkar, Dhiman; Deshpande, Mukund V.; Joshi, Swati P. (Natural Product Research, 2014)
From the red coloured extract (Kamala) prepared through acetone extraction of the fresh whole uncrushed fruits of Mallotus philippinensis, one new dimeric chalcone (1) along with three known compounds 1-(5,7-dihydroxy-2,2,6-trimethyl-2H-1-benzopyran-8-yl)-3-phenyl-2-propen -1-one (2), rottlerin (3) and 4 `-hydroxyrottlerin (4) were isolated. The structure of compound 1 was elucidated by 1D and 2D NMR analyses that included HSQC, HMBC, COSY and ROESY experiments along with the literature comparison. Compounds 1-4 were evaluated for antifungal activity against different human pathogenic yeasts and filamentous fungi. The antiproliferative activity of the compounds was evaluated against Thp-1 cell lines. Compounds 1 and 2 both exhibited IC50 of 8, 4 and 16 mu g/mL against Cryptococcus neoformans PRL518, C. neoformans ATCC32045 and Aspergillus fumigatus, respectively. Compound 4, at 100 mu g/mL, showed 54% growth inhibition of Thp-1 cell lines.
Keywords: 4 `-hydroxyrottlerin; antifungal; dimeric chalcone; kamalachalcone E; Mallotus philippinensis; rottlerin

Highly efficient one-pot multi-component synthesis of alpha-aminophosphonates and bis-alpha-aminophosphonates catalyzed by heterogeneous reusable silica supported dodecatungstophosphoric acid (DTP/SiO2) at ambient temperature and their antitubercular eval - Mulla, Shafeek Abdul Rashid; Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Gample, Suvarna P.; Sarkar, Dhiman (RSC Advances, 2014)
A highly efficient one-pot multi-component reaction (MCR) protocol over DTP/SiO2 has been developed for the synthesis of alpha-aminophosphonate derivatives (4a-x) in excellent yields. The alpha-aminophosphonate derivatives were for the first time evaluated for their antitubercular activity against the M. tuberculosis H37Ra (MTB) strain. An evaluation of the data on the cytotoxicity and antimicrobial activity shows that 4n and 4v are promising antitubercular agents.